2015
DOI: 10.3389/fpsyg.2015.01680
|View full text |Cite
|
Sign up to set email alerts
|

The curvilinear relationship between work pressure and momentary task performance: the role of state and trait core self-evaluations

Abstract: Whereas several studies have demonstrated that core self-evaluations (CSE)–or one’s appraisals about one’s own self-worth, capabilities, and competences–relate to job outcomes, less is known about the mechanisms underlying these relationships. In the present study, we address this issue by examining the role of within- and between-person variation in CSE in the relationship between work pressure and task performance. We hypothesized that (a) work pressure relates to task performance in a curvilinear way, (b) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 55 publications
0
28
1
Order By: Relevance
“…Despite the importance of curvilinear relationship, it comes as some surprise that curvilinear moderation-a statistical model that identifies differences in the strength and direction of curvilinearity between X and Y across the levels of M-is neither commonly used by researchers nor has it received the attention in the literature that it deserves. As noted in Hofmans et al [13], the inverted U shape between work pressure and performance may differ across different personality traits (e.g., high versus low CSE). Afshar et al [20] further found that people with maladaptive personality traits (e.g., neuroticism) tend to form a more flattened, inverted U-shape relationship between stress and performance, whereas people with adaptive personality traits (e.g., openness) tend to form the usual inverted U shape between stress and performance as stated in the Yerkets-Dodson Law.…”
Section: Conclusion and Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Despite the importance of curvilinear relationship, it comes as some surprise that curvilinear moderation-a statistical model that identifies differences in the strength and direction of curvilinearity between X and Y across the levels of M-is neither commonly used by researchers nor has it received the attention in the literature that it deserves. As noted in Hofmans et al [13], the inverted U shape between work pressure and performance may differ across different personality traits (e.g., high versus low CSE). Afshar et al [20] further found that people with maladaptive personality traits (e.g., neuroticism) tend to form a more flattened, inverted U-shape relationship between stress and performance, whereas people with adaptive personality traits (e.g., openness) tend to form the usual inverted U shape between stress and performance as stated in the Yerkets-Dodson Law.…”
Section: Conclusion and Discussionmentioning
confidence: 85%
“…The rationale is that researchers should focus on the critical M values (e.g., personality trait) that substantially and significantly change the (simple) slope values regressing Y (e.g., performance) on X (e.g., work pressure), which is important for theory and model testing in behavioral sciences. For example, Hofmans et al [13] stated that the existing literature often focused on linear moderation, and hence, they examined if there exists any curvilinear relationship between work pressure and momentary task performance, and how this relationship can be moderated by one's personality trait (e.g., core self-evaluations [CSE], i.e., one's appraisals about self-worth, capabilities, and competency). They found that people with a high level of CSE are less affected by work pressure (i.e., a more flattened, inverted U shape between pressure and performance) than people with a low level of CSE (i.e., a more leptokurtic, inverted U shape between pressure and performance).…”
Section: Linear Moderation (Categorical and Continuous)mentioning
confidence: 99%
“…Thus, when job demands increase, they become negative, and may lead to work intensification, a process linked to exhaustion and burnout (Granter, McCann, & Boyle, ; Paškvan et al, ). In line with this reasoning, the research of Hofmans et al () and Paškvan and colleagues (2016) indeed showed that when job demands become too high, workers are likely to perceive this as too challenging and essentially hindering their performance. We therefore expect that high job demands will be related to higher susceptibility of breach and violation over time.…”
Section: Theoretical Backgroundmentioning
confidence: 86%
“…Scholars already found support for a curvilinear relationship between workload and other outcome variables, such as physical health (i.e., cross-sectional study; Karanika-Murray et al, 2009) and task performance (i.e., diary study; Hofmans et al, 2015). In line with the Yerkes-Dodson law (Yerkes and Dodson, 1908) and activation theory (Gardner, 1986; Gardner and Cummings, 1988), scholars found that high, low and moderate levels of workload were in decreasing order related to negative health outcomes (Shultz et al, 2010).…”
Section: Introductionmentioning
confidence: 99%